Determination of proteolytic activity in cereals - D. Wojciechowska; J. Kączkowski (Acta Societatis Botanicorum Poloniae, 2015)
Results have been presented indicating that native proteolytic enzymes and bromelain acted variously ion wheat proteins differentiated in quality, they also act nonspecifically ton haemoglobin. It was thought useful to elaborate a new method of proteolytic activity determination based on the application of a standard natural substrate. The latter consists of gluten extract in acetic acid from a definite flour sample. The method of substrate selection and the determination procedure are described and some examples of wheat proteolytic activity determination are given.